Computer-assisted and robotic endoscopy : Second International Workshop, CARE 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 5, 2015 : revised selected papers /: Second International Workshop, CARE 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 5, 2015 : revised selected papers. ([2016]) - Unknown
No abstract available